The Impact of Customer Experience and Trust on WOM through Customer Satisfaction among Students at Ma Chung University Malang - Ratri, Wahyu Dianing; Supriadi, Bambang; Broto, Felik Sad Windu Wisnu (International Journal of Business and Applied Economics, 2024)
In the highly competitive landscape of higher education, institutions must provide quality services to attract and retain students. Continuous evaluation of student perceptions and satisfaction is crucial to ensure the sustainability and competitive edge of higher education institutions. This study aims to analyze the impact of Customer Experience and Trust on Customer Satisfaction, as well as the influence of Customer Satisfaction on Word of Mouth (WOM) within a university setting. This research is explanatory, employing quantitative methods and a survey approach. Data analysis was conducted using Descriptive Analysis and Structural Equation Modeling. The findings show that students have positive experiences with Ma Chung and trust the services provided by the faculty and staff, contributing to their overall satisfaction. These experiences and trust significantly influence students' tendencies to share positive information about Ma Chung with others (WOM). Additionally, Customer Experience and Trust also affect WOM through the mediation of Customer Satisfaction. Students' experiences and trust in Ma Chung's services significantly enhance their satisfaction, which in turn encourages them to recommend the university to others. This study highlights the importance of improving student experiences and trust to strengthen positive WOM.